Evaluation of single nucleotide variants in intron 1 of the ABO Gene as diagnostic markers for the A1 blood group - Bugert, Peter; Rink, Gabriele; Klüter, Harald (Transfusion medicine and hemotherapy, 2023)
Introduction: The molecular diagnosis of the A1 blood group is based on the exclusion of ABO gene variants causing blood groups A2, B, or O. A specific genetic marker for the A1 blood group is still missing. Recently, long-read ABO sequencing revealed four sequence variations in intron 1 as promising markers for the ABO*A1 allele. Here, we evaluated the diagnostic values of the 4 variants in blood donors with regular and weak A phenotypes and genotypes. Methods: ABO phenotype data (A, B, AB, or O) were taken from the blood donor files. The ABO genotypes (low resolution) were known from a previous study and included the variants c.261delG, c.802G>A, c.803G>C, and c.1061delC. ABO variant alleles (ABO*AW.06,*AW.08,*AW.09,*AW.13, *AW.30, and *A3.02) were identified in weak A donors by sequencing the ABO exons before. For genotyping of the ABO intron 1 variants rs532436, rs1554760445, rs507666, and rs2519093, we applied TaqMan assays with endpoint fluorescence detection according to a standard protocol. Genotypes of the variants were compared with the ABO phenotype and genotype. Evaluation of diagnostic performance included sensitivity, specificity, positive (PPV), and negative predictive value (NPV). Results: In 1,330 blood donors with regular ABO phenotypes and genotypes, the intron 1 variants were significantly associated with the proposed A1 blood group. In 15 donors, we found discrepancies to the genotype of at least one of the 4 variants. For the diagnosis of the ABO*A1 allele, the variants showed 98.79-99.48% sensitivity, 99.66-99.81% specificity, 98.80-99.31% PPV, and 99.66-99.86% NPV. Regarding the A phenotype, the diagnostic values were 99.02-99.41% sensitivity, 99.63-99.76% specificity, 99.41-99.61% PPV, and 99.39-99.63% NPV. The *A1 marker allele of all intron 1 variants was also associated with the *AW.06, *AW.13, and *AW.30 variants. Samples with *AW.08, *AW.09, and *A3.02 variants lacked this association. Conclusion: The ABO intron 1 variants revealed significant association with the ABO*A1 allele and the A phenotype. However, the intron 1 genotype does not exclude variant alleles causing weak A phenotypes. With the introduction of reliable tag, single nucleotide variants for the A1, A2, B, and O blood groups and the genotyping instead of phenotyping of the ABO blood group are getting more feasible on a routine basis.